Savings and Loan Transaction Agreement from the Perspective of Islamic Business Ethics - Mardhatila; Muhamad Aji Purwanto (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
UED-SP Barokah Mandiri, owned by the village government, is one of the choices often used as a place for borrowing funds by the community. However, the contract agreement used is conventional. So, there are many perceptions that those who are not Sharia are not that good. This raises the question of whether it is true that conventionally based agreements are not good. In order to see this, the researcher will examine the model of the contract agreement carried out by UED-SP and its services to prospective/customers from the perspective of Islamic business ethics. The research method used is field research with a qualitative descriptive approach. The data analysis model uses inductive reasoning. Data sources were obtained from front liners, heads, customers and prospective UED-SP Barokah Mandiri Penampi Village customers and documents. The research location is the Penampi Village area, precisely at UED-SP Barokah Mandiri, Penampi Village. The data analysis model used is descriptive qualitative. The choice of this method was to analyze and explain the phenomenon or social condition of the people of Penampi Village who work as farmers and need a source of funds. However, the closest financial institution there is a conventional financial institution. The results of the study show that in terms of business ethics, the agreements and services carried out by UED-SP Barokah Mandiri are more or less compatible with the values of Islamic business ethics.